Hubungan Pekerjaan dan Jadwal Kerja dengan Indeks Massa Tubuh Balita di Wilayah Kerja Puskesmas Yosodadi Kota Metro - Rilyani Rilyani; Lidya Aryanti; Calvyn Reza Trisnantyas (Universitas Malahayati Lampung, 2022)
ABSTRACT: EMPLOYMENT RELATIONSHIP AND WORKING SCHEDULE WITH BODY MASS INDEX IN YOSODADI PUSKESMAS WORKING AREA METRO CITY Introduction: The coverage of children under five in Lampung Province in 2019 was 79%, and this figure was above the target (76.18%). This figure illustrates that participation from the community to come to posyandu is still quite good in Lampung Province, while for Metro City the percentage of data is weighted at 78.8%. Data obtained through the Metro City Health Office in 2020 at the Yosodadi Health Center obtained as many as 656 toddlers aged 1-5 years who were weighingObjective: To find out the relationship between work and work schedule with the body mass index of toddlers aged 1-5 years.Methods: This type of research is quantitative. The design in this study uses an analytical survey design with a cross-sectional approach. The population is mothers and children aged 3-5 years, which is then calculated using the Slovin formula to obtain 197 children. Sampling technique purposive sampling Analysis of univariate and bivariate data using the chi-square test.Results: working mothers as many as 107 respondents (54.3%)., standard work schedule is 8 hours per day as many as 109 respondents (55.3%), BMI is not ideal, namely 18.5 and 22.9 as many as 103 respondents ( 52.3%. The results of statistical tests using the chi-square test obtained p-value = 0.000 (α0.05), p-value = 0.085 (α0.05).Conclusion: The results of statistical tests using the chi-square test obtained p-value = 0.000 (α0.05) which means the relationship between mother's work and body mass index of toddlers aged 3-5. The p-value = 0.085 (α0.05) means that there is no relationship between the mother's work schedule and the body mass index of children aged 3-5 years. It is recommended that parents who have toddlers with underweight and obese nutritional status should pay more attention to parenting patterns Keywords : Mother's Work Work Schedule, Toddler Body Mass Index INTISARI: HUBUNGAN PEKERJAAN DAN JADWAL KERJA DENGAN INDEKS MASSA TUBUH BALITA DI WILAYAH KERJA PUSKESMAS YOSODADI KOTA METRO Pendahuluan: Cakupan balita ditimbang di Provinsi lampung tahun 2019 sebesar 79 %, dimana angka ini diatas target (76,18%). Angka ini menggambarkan bahwa partisipasi dari masyarakat untuk datang ke posyandu masih cukup baik di Provinsi Lampung, sedangkan untuk Kota Metro persentase data ditimbang sebesar 78,8%. Data yang diperoleh melalui Dinkes Kota Metro tahun 2020 di Puskesmas Yosodadi didapat sebanyak 656 balita usia 1-5 tahun yang melakukan penimbangan berat badanTujuan: Diketahui hubungan pekerjaan dan jadwal kerja dengan indeks massa tubuh balita usia 1-5 tahun.Metode: Jenis penelitian kuantitatif, Rancangan dalam penelitian ini menggunakan desain Survei Analitik dengan pendekatan cross sectional. Populasi adalah ibu dan anak usia 3-5 tahun, yang kemudian dilakukan perhitungan sampel dengan rumus slovin didapat sebanyak 197 anak. Teknik sampling purposive sampling Analisa data univariat dan bivariat menggunakan uji chi square.Hasil : ibu bekerja sebanyak 107 responden (54,3%)., jadwal kerja standar yaitu 8 jam per hari sebanyak 109 responden (55,3%), IMT tidak ideal yaitu 18,5 dan 22,9 sebanyak 103 responden (52,3%). Hasil uji statistik menggunakan uji chi square didapat nilai p-value = 0.000 (α0.05), nilai p-value = 0.085 (α0.05).Kesimpulan : Hasil uji statistik menggunakan uji chi square didapat nilai p-value = 0.000 (α0.05) yang artinya ada hubungan pekerjaan ibu dengan indeks massa tubuh balita usia 3-5. Nilai p-value = 0.085 (α0.05) yang artinya tidak ada hubungan jadwal kerja ibu dengan indeks massa tubuh balita usia 3-5 tahun. Disarankan kepada orang tua yang memiliki balita dengan status gizi kurus dan gemuk, harus lebih memperhatikan lagi mengenai pola asuh anak Kata Kunci : Pekerjaan Ibu Jadwal Kerja, Indeks Masa Tubuh Balita